La couverture de presse et ses fonctions légitimantes - Crelinsten, Ronald (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1987)
This paper examines the legitimating function of press coverage by means of a specific case study of political violence. Dissident actors who resort to violence to achieve their political goals are generally treated by the authorities as common criminals. This criminal justice model is reproduced and reinforced in the press by selective focus on specific, narrow topics at the expense of political analysis. These topics include the victims, the threat of future attacks, police activity, and the declarations of those in authority. In the October Crisis of 1970, this process was temporarily disrupted and a transient symmetry was achieved whereby the point of view of the dissident actors and their supporters received as much attention as the official perspective of the authorities. With the invocation of the War Measures Act, this symmetry was destroyed and press coverage once again returned to an almost exclusive focus on official definitions of the situation. The author suggests that this pattern of press coverage reflects a transient disruption in the legitimating function of the media whereby, in normal times, the reporting of “news” can reproduce and reinforce official views of dissident actors who use violence for political ends.